2019
DOI: 10.1101/756452
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pulling the strings of cell cycle: a non-coding RNA, CcnA, modulates the master regulators CtrA and GcrA in Caulobacter crescentus

Abstract: 20Bacterial cells are powerful models for understanding how cells divide and accomplish global 21 regulatory programs. In Caulobacter crescentus a cascade of essential master regulators regulate the 22 correct and sequential activation of DNA replication, cell division and development of different cell 23 types. Among them CtrA plays a crucial role coordinating all those functions. Despite decades of 24 investigation, no control by non-coding RNAs (ncRNAs) has been linked to Caulobacter cell cycle. 25Here, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 91 publications
(183 reference statements)
1
3
0
Order By: Relevance
“…This, in turn, could inhibit the PTS Ntr relay, limiting (p)ppGpp and delaying the progression of the cell cycle ( 56 , 65 , 66 ). This is also in agreement with the upregulation of the cell-cycle-regulated sRNA CcnA, which also leads to a decrease in the growth rate ( 52 ).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This, in turn, could inhibit the PTS Ntr relay, limiting (p)ppGpp and delaying the progression of the cell cycle ( 56 , 65 , 66 ). This is also in agreement with the upregulation of the cell-cycle-regulated sRNA CcnA, which also leads to a decrease in the growth rate ( 52 ).…”
Section: Discussionsupporting
confidence: 82%
“…Although the gene for the RNA chaperone Hfq was not differentially expressed, previous studies have shown that it participates in this type of regulation, acting as an intermediate between the sRNA and its target ( 50 , 51 ). Among the most upregulated sRNAs is the cell cycle-regulated CcnA (R0094) (11-fold), which is responsible for controlling two master regulators of the cell cycle, CtrA and GcrA ( 52 ). As the overexpression of CcnA leads to a slow growth phenotype ( 52 ), it is tempting to speculate that it contributes to the decrease in growth rates observed at low temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heatmap figure was obtained with the R package Pheatmap and integrates the above annotations with gene expression data in the present work ( S12 Fig ). All fastQ files are available from the Dryad database (doi: 10.5061/dryad.4mw6m909k ) [ 88 ].…”
Section: Methodsmentioning
confidence: 99%